CLINICAL AND FUNCTIONAL EFFECTIVENESS AND SAFETY OF HIGH-FREQUENCY OSCILLATION OF CHEST WITH «THE VEST AIRWAY CLEARANCE SYSTEM» IN CHILDREN WITH CYSTIC FIBROSIS - N.Yu. Kashirskaya; N.I. Kapranov; T.A. Bogdanova ("Paediatrician" Publishers LLC, 2010)
Authors present results of treatment of 60 patients with cystic fibrosis 1-17 years old with «The Vest Airway Clearance System». Method of high-frequency oscillation of chest increases volume of moved off phlegm and improves functional abilities of lungs. This method can be used in younger children and in patients regardless of age in poor condition who can't actively carry out drainage of phlegm and respiratory exercises. Key words: children, cystic fibrosis, high-frequency oscillation of chest, treatment. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(5):67-71)